Accounting and analytical problems of cultural heritage security in Polish-Ukrainian cross-border cooperation - Shvets, V. (Видавництво Львівської політехніки, 2020)
The safety of cultural heritage in a cross-border dimension depends significantly on the influence of accounting and analytical factors, as they form the basis for the perception of its objects for their proper preservation and constant monitoring of the state and risks of irreversible changes. This issue is especially important in Polish-Ukrainian cross-border cooperation, where historical realities have led to the destruction and destruction of many cultural heritage sites. Accounting and analytical problems of cultural heritage safety arise both in connection with the lack of theoretical and methodological studies of these issues and due to the imperfection of the legal and regulatory field, especially in Ukraine. It is substantiated that the main problem of theoretical and methodological character is the lack of studies aimed at developing a standard system of perception of cultural heritage objects in the PolishUkrainian border area. The results of the analysis of the main criteria of the system of perception used in accounting for cultural heritage objects, the example of intangible monuments, the absence of scientifically substantiated species and varieties, which complicates the use of standard methods and techniques of accounting and analytical nature. First of all, the standardization of the classification parameters of cultural heritage objects, taking into account the national priorities of Ukraine and Poland, requires scientific study. It is also established that the positive changes made in recent years in the legal support for the preservation of the common cultural heritage have in their tools accounting and analytical aspects that can significantly affect their objective perception for exercising constant control. In the context of solving accounting and analytical problems, it is necessary to develop a methodology for objective evaluation of cultural heritage objects, taking into account the prospect of world cultural and historical progress. Addressing these issues also involves taking into account the achievements of Poland in the classification of cultural and historical sites, as well as those initiatives for the protection of the common cultural and historical heritage concerning sites located in the adjacent border area.
Keywords: accounting and analytical issues; cultural heritage; Polish-Ukrainian cross-border cooperation; security; M41; 657; 339.137 (477.87)